Vegetasi Sagu (Metroxylon sagus.Rottb) di Daerah Teluk Kabung Kodya Padang - Nurliati Nurliati (Pendidikan Biologi FKIP UMMY, 2019)
Sago (Metroxylon spp.) Is a plant from family palmae Yang has a Major Role hearts Sufficient supply of carbohydrate source potential in Indonesia, especially the eastern part of Indonesia Up When husband is still not used optimally. * According to the Central Bureau of Statistics (1982) Needs sago flour in Indonesia Approximately 59,400 tons / year ,. Data is based on corn starch production of different types / varieties of corn ranged between 5-19 tonnes / ha / year. Means not meet domestic Purposes In Every Consumer Year. Based on the problems in differences So researchers are encouraged to review determine vegetation Sago (Metroxylon Sagus Rottb) in the Gulf Region Kabung Padang Municipality. Research is a problem: How can the state of vegetation Sago (Metroxylon Sagus Rottb) IN area is Bungus sackcloth Bay Padang end-type What type of plants that exist on vegetation Sago (Metroxylon Sagus Rottb) IN area is Bungus sackcloth Bay Padang. The research goal is to review the husband know objec vegetation Sago (Metroxylon Sagus Rottb) IN area is Bungus sackcloth Bay Padang And for a review to know types plant vegetation that existed at Sago (Metroxylon Sagus Rottb) in area is Bungus sackcloth Bay Padang. BY initial research survey methods. To determine the type of vegetation sago of the Bungus sackcloth bay area is the Municipality of Padang. The research results implemented the sackcloth Bay area is Padang municipality is as follows: Conclusion Research is 1.Keadaan vegetation Sago (Metroxylon Sagus Rottb) in area is research is homogeneous density. Based on the survey findings are then encountered vegetation around the swamp forest vegetation Sago (Metroxylon Sagus Rottb) is: a. Oncosperma tigillarium. b. Acanthus ilicifolius. c. Pandanus tectorius. d. Dillenia sp. e. Nauclea sp, f. Polypodium spp, g. Dendrobium sp, h. Syngonium podophyllum, i. Cyperus sp end poaceae